A team is not always a dream: How can coaches reduce social loafing in team sports? - de Backer, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Like managers, coaches have to distinguish between players in terms of functions, status, etc. This differentiation leads to concerns about a fair treatment, usually referred to as organizational justice. Studies in business contexts have continually demonstrated the power of justice judgments to shape people`s thoughts, feelings, and actions. Consequently, this research aims at testing the relationship between coach-related justice and a behavior-related variable (i.e., social loafing) in elite sport teams. Social loafing has been defined as the reduction in motivation and effort when individuals work collectively, compared with when they work individually (Latane, 1979) and will usually result in a decreased team performance. However, we are not simply interested in the direct relation between coach characteristics and the individual behavior of athletes. The main purpose of this study is to develop a model that explains the effects of perceived justice of the coach on a series of intervening group-oriented variables (i.e., the motivational climate, team identification and team cohesion) leading to perceived and selfreported social loafing in interactive sport teams. Method Norwegian top level female handball players (N = 110; M = 22.8) filled in mail surveys assessing perceived justice, the motivational climate, team identification, team cohesion, and social loafing. Structural equation modeling (i.e., both confirmatory and exploratory) was used to investigate our research model. Results The confirmatory path analysis indicated a poor fit of the hypothesized model (ƒÔ2 = 64.52, df = 22, p = .00; GFI = .90; AGFI = .80; CFI = .84; RMSEA = .14). Consequently, an exploratory path analysis was performed using structural equation modeling. Results of the revised model provided a good fit to the data (ƒÔ2 = 33.45, df = 19, p = .02; GFI = .94; AGFI = .86; CFI = .95; RMSEA = .08). Discussion The revised model showed that the more the coach is perceived as fair, the more a mastery climate is experienced and the less and an ego-oriented climate. A mastery climate in turn was positively related to athletes` team identification, while a performance climate was not significant related to it. Furthermore, our results confirmed that task and not social cohesion mediates the relation between team identification and both forms of social loafing in elite female sport teams. From a more practical standpoint, our results showed that the coach himself can guide the group processes and consequently reduce social loafing, even in world-class teams.